Laser R-Test for Angular Positioning Calibration and Compensation of the Five-Axis Machine Tools - Cao-Sang Tran; Tung-Hsien Hsieh; Wen-Yuh Jywe (Applied Sciences, 2021)
The angular positioning error of the rotary stage causes low quality in milling various angles of a workpiece. This study proposes a solution that could improve these issues by using our Laser R-test for angular positioning calibration and compensation of the five-axis machine tools in compliance with the simultaneous measurement path of ISO regulations: ISO 10791-6 and ISO 230-2. System uncertainty analysis and calibration were implemented for system prediction. The measurement method proposed in this paper could solve concentricity problems between measurement devices and the rotary table by applying the Cosine theorem with a Cartesian coordinate system. Further, we used the commercial instrument XR20-W (Renishaw, UK) rotary axis calibrator to verify and compare the measured results on a CNC machine tool. The applied system achieves an angular error of 0.0121 degrees for actual workpieces and is smaller than the referring commercial system, which achieves an error of about 0.0022 degrees. The system in this research is useful for five-axis machine tool full calibrations.